Perilaku Pemeriksaan Antenatal Care pada Ibu Hamil Trimester III di Praktek Mandiri Bidan Wulan Rahma Jodipan Kota Malang - Betha Putri Savina; Swito Prastiwi; Dyah Widodo; Gita Kostania (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Antenatal care (ANC) examinations in Indonesia are still below the standard coverage of recommended visits, placing pregnant women who do not complete examinations at risk of health problems for both mother and fetus due to late detection. ANC serves as an initial screening for maternal and fetal conditions and is influenced by knowledge, attitudes, and behavior of pregnant women. This study aimed to identify ANC examination behavior among third-trimester pregnant women at PMB Wulan Rahma. This research used a descriptive design with a sample of 15 third-trimester pregnant women selected through purposive sampling. Data were collected using questionnaires and observation sheets and analyzed using univariate analysis. The study was conducted at TPMB Wulan Rahma Jodipan, Malang City in August 2024. The results showed that all respondents had good knowledge and positive attitudes toward ANC examinations. Most pregnant women consistently carried out ANC visits, indicating generally good ANC examination behavior. In conclusion, the majority of third-trimester pregnant women demonstrated good antenatal care behavior. Future research is recommended to explore other factors influencing ANC behavior, including individual, social, environmental, and healthcare service factors.